Short Term Fate of Great Saphenous Vein after Radiofrequency Ablation for Varicose Veins - Karmacharya, R.M.; Devbhandari, M; Shakya, Y.R. (Kathmandu University Medical Journal, 2017)
Background Radiofrequency ablation of varicose vein have gained popularity compared to conventional surgery due to comparable long term results in addition to definite immediate superiorities. This modality has been started in Nepal since August 2003 and the study on short term fate of ablated vein segment confirms the anatomical benefit in addition to the clinical benefit. Objective To analyze short term fate of segment of great saphenous vein that has been treated by Radiofrequency ablation in terms of occlusion of saphenofemoral junction and absence of recanalisation on Doppler ultrasonography finding done at 3-6 months postoperative period. Method Total 81 cases subjected for radiofrequency ablation of great saphenous vein in thigh segment during August 2013 – September 2014 were followed up in between 3 to 6 months by Doppler ultrasonography. The findings were classified into type 1 to 4 results based on the anatomic closure of saphenofemoral junction and absence of recanalisation on treated segments. Result There were total 81 cases with 54.3% female and 45.7% male patients. Mean short term follow up duration was 4.9 months (S.D. 1.1 months). Great Saphenous Vein was cannulated most frequently in between 5 cm above knee to 5 cm below knee. Mean number of Radio Frequency Ablation (RFA) segments were 6.6 (SD=3.1). There was complete occlusion (Type 1 results) in 51 cases (63.0%). In 24 cases (29.6%) there was competent saphenofemoral junction with partial recanalisation in distal part of Great Saphenous Vein (GSV) (Type 2 results). In six cases (7.4%) there was incompetent saphenofemoral junction with partial recanalisation in distal part of Great Saphenous Vein (Type 3 results). There were no cases with incompetent saphenofemoral junction with complete recanalisation in distal part of Great Saphenous Vein (Type 4 results). Conclusion Radio Frequency Ablation for varicose vein, besides making clinical improvements, is also associated with good anatomical results.